Analysis Of A Bearingless Permanent Magnet Synchronous Motor - Mamat, Normaisharah; Abdul Karim, Kasrul; Ibrahim, Zulkifilie; Ahmad Tarusan, Siti Azura; Mat Lazi , Jurifa; Yusup Lada, Musa (Publications International, 2014)
Bearingless permanent magnet synchronous motor (BPMSM) is known as both conventional permanent magnet synchronous motor and traditional magnetic bearings. For the purpose of this paper, the design and analysis of BPMSM using a Matlab/Simulink and 2-D ANSYS Maxwell are presented. The principle of electromagnetic force is utilized to ensure a stable levitation operation of BPMSM. The BPMSM mathematical model that is established to represent the dynamic of motoring force and radial suspension force is simulated in Matlab/Simulink environment. The ANSYS Maxwell, as an accurate finite element method (FEM) software in solving static, frequency-domain, and time-varying electromagnetic and electric fields is used to assist the development of the BPMSM model before the integration with the control system is performed. The excitation of motoring winding and suspension winding are independently controlled through separate PI controller. The applications for BPMSM are suitable for high speed electrical machines such as compressors, turbines, pumps, and mixers.